And then it's spring - Fogliano, Julie; Stead, Erin E. (New York : Roaring Brook Press, 2012)
Simple text reveals the anticipation of a boy who, having planted seeds while everything around is brown, fears that something has gone wrong until, at last, the world turns green.
School Library Journal starred, January 2012.
Booklist starred, December 2011.
Horn Book Starred, January 2012.
Pub Weekly, December 2011.
Kirkus Starred, January 2012.
Horn Book, January 2012.
Keywords: Spring -- Juvenile fiction; Gardens -- Juvenile fiction; Spring -- Fiction; Gardens -- Fiction; Spring -- Fiction; Gardens -- Fiction; Spring -- Fiction